Blast Mitigation Experimental and Numerical Studies - Shukla, Arun; Rajapakse, Yapa D. S.; Hynes, Mary Ellen (Springer New York : Imprint: Springer, 2014)
Blast Mitigation: Experimental and Numerical Studies covers both experimental and numerical aspects of material and structural response to dynamic blast loads and its mitigation. The authors present the most up-to-date understanding from laboratory studies and computational analysis for researchers working in the field of blast loadings and their effect on material and structural failure,  develop designs for  lighter and highly efficient structural members for blast energy absorption, discuss vulnerability of underground structures, present methods for dampening blast overpressures, discuss structural post blast collapse and give attention to underwater explosion and implosion effects on submerged infrastructure and mitigation measures for this environment. This book also: Presents experimental methods of material and structural response to dynamic blast loads Includes computational analysis of material and structural response to dynamic blast loads Offers mitigation measures for structures in various environments Relates lab experiments to larger field tests Features more than 150 illustrations Blast Mitigation: Experimental and Numerical Studies is an ideal book for graduate students, practicing engineers and researchers working in the field of blast mitigation.